Commentary on 'Changing prevalence of diabetes mellitus in bullous pemphigoid: it is the dipeptidyl peptidase‐4 inhibitors'. (3rd May 2018) - Fania, L.; Di Zenzo, G.; Mazzanti, C.; Abeni, D.
Abstract : Linked article: This article is commented on by A. Gravani et al., pp. e438–e439 in this issue. To view this article visithttps://doi.org/10.1111/jdv.14957